Odpowiedzi

2009-10-08T17:29:33+02:00
A={0, 3, 6, 9, 12, ...} B={0, 1, 2, 3, 4, 5, ...}
A={-6, -4, -2, 0, 2, 4, 6}, B- zbiór liczb naturalnych parzystych

A suma zbiorów B
a)A u B = {0, 1, 2, 3, 4, ...} inaczej: A u B = {x ∈ C: x ≥ 0}
b)A u B = {-6, -4, -2, 0, 2, 4, 6, 8, ...} inaczej: A u B = {x ∈ C: x ≥ -6 i 2|x}

A iloczyn zbiorów B
a)A n B = {0, 3, 6, 9, 12, ...} inaczej: A n B = {x ∈ C: x ≥ 0 i 3|x}
b)
A n B = {0, 2, 4, 6} - dla 0 ∈ N lub A n B = {2, 4, 6} - dla 0 ∉ N

A-B
a) A-B - zbiór pusty
b) A-B = {-6, -4, -2} - dla 0 ∈ N lub A-B = {-6, -4, -2, 0} - dla 0 ∉ N

B-A
a)B-A = {1, 2, 4, 5, ...} inaczej: A n B = {x ∈ N: ~(3|x)}
b)B-A = {x ∈ C: (x < -6 ∨ x > 6) i 2|x}
2009-10-08T17:39:46+02:00
A={0, 3, 6, 9, 12, ...} B={0, 1, 2, 3, 4, 5, ...}

a)A u B = {0, 1, 2, 3, 4, ...}
A n B = {0, 3, 6, 9, 12, ...} =A
A-B - zbiór pusty
B-A = {1, 2, 4, 5, ...}

A={-6, -4, -2, 0, 2, 4, 6}, B- zbiór liczb naturalnych parzystych
b)A u B = {-6, -4, -2, 0, 2, 4, 6, 8, ...}
A n B = {0, 2, 4, 6}
A-B = {-6, -4, -2}
B-A = {8,10,12...}